Work-life balance dimensions and their association with mental health among working mothers: a systematic review - Nofita Lindriani; Eval Edmizal (Journal of Counseling, Education and Society, 2026)
Working mothers often experience competing demands between occupational and family responsibilities, which may adversely affect their mental health. However, evidence regarding the work-life balance dimensions associated with these outcomes remains fragmented. This systematic literature review synthesized evidence on how work-life balance, work-family conflict, family-to-work conflict, organizational support, and occupational context influence the mental health of working mothers. Following the PRISMA 2020 guidelines, a Scopus search identified 200 records published between 2020 and 2026. After screening based on language, publication type, and eligibility criteria, 167 studies were included in the qualitative synthesis. Methodological quality was assessed using the FICO framework, and only studies meeting the predefined quality threshold were retained. Thematic synthesis revealed four major findings. First, work-family conflict and family-to-work conflict were consistently associated with depression, anxiety, burnout, and psychological distress. Second, occupation-specific stressors, particularly in healthcare and information technology, intensified mental health risks. Third, organizational support, flexible work arrangements, family support, and psychological resilience acted as protective factors that mitigated the negative effects of role conflict. Finally, persistent gender norms, including maternal guilt and the “supermom” expectation, continued to shape working mothers' psychological well-being. These findings suggest that existing theoretical frameworks should be complemented with context-sensitive perspectives and that family-friendly workplace policies must be accompanied by greater gender equality in domestic responsibilities. Future research should prioritize longitudinal, cross-national, and intervention-based studies to strengthen the evidence base.